Ticks and Tick-Borne Pathogens in Domestic Animals, Wild Pigs, and Off-Host Environmental Sampling in Guam, USA - Weaver, Genevieve V.; Anderson, Neil; Garrett, Kayla; Thompson, Alec T.; Yabsley, Michael J. (Frontiers in Veterinary Science, 2022)
Background: Guam, a United States of America (USA) island territory in the Pacific Ocean is known to have large populations of ticks; however, it is unclear what the risk is to wildlife and humans living on the island. Dog (Canis familiaris), cat (Felis catus), and wild pig (Sus scrofa) sentinels were examined for ticks, and environmental sampling was conducted to determine the ticks present in Guam and the prevalence of tick-borne pathogens in hosts. Methods and Results: From March 2019-November 2020, ticks were collected from environmental sampling, dogs, cats, and wild pigs. Blood samples were also taken from a subset of animals. 99 ticks were collected from 27 environmental samples and identified as Rhipicephalus sanguineus, the brown dog tick. Most ticks were collected during the dry season with a success rate of 78.6% (95% CI: 49.2-95.3). 6,614 dogs were examined, and 12.6% (95% CI: 11.8-13.4) were infested with at least one tick. 1,112 cats were examined, and six were found with ticks. 17.2 % (95% CI: 9.5-27.8) of wild pigs had ticks. In total, 1,956 ticks were collected and 97.4% of ticks were R. sanguineus. The other tick species found were Rhipicephalus microplus (0.77%), Amblyomma breviscutatum (0.77 %), and a Haemaphysalis sp. (0.51%). Blood samples from 136 dogs, four cats, and 64 wild pigs were tested using polymerase chain reaction (PCR) and DNA sequencing methods. Five different tick-borne pathogens with the following prevalences were found in dog sentinels: Anaplasma phagocytophilum 5.9% (95% CI: 2.6-11.3); Anaplasma platys 19.1% (95% CI: 12.9-26.7); Babesia canis vogeli 8.8% (95% CI: 4.6-14.9); Ehrlichia canis 12.5% (95% CI: 7.5-19.3); Hepatozoon canis 14.7% (95% CI: 9.2-28.8). E. canis was detected in one cat, and no tick-borne pathogens were detected in wild pigs. Overall, 43.4% (95% CI: 34.9-52.1) of dog sentinels had at least one tick-borne pathogen. Serological testing for Ehlrichia spp. and Anaplasma spp. antibodies showed prevalences of 14.7% (95% CI: 9.2-28.8) and 31.6% (95% CI: 23.9-40) respectively. Conclusion: Four different ticks were found in Guam to include a Haemaphysalis sp., previously unreported. Dogs with ticks have a high prevalence of TBP which makes them useful sentinels.